(untitled) (diségno, 2024)
The use of analog models in microarchitecture design offers a series of benefits, from detailed exploration of small-scale elements to stimulating creativity and innovation. These enriching experiences significantly contribute to the design process and help develop more robust and effective architectural solutions. Models are tools that enhance haptic perception and play various roles in the analysis, experimentation, conceptualization, and teaching of microarchitectures. Their ability to provide a tangible and accessible representation of design makes them remarkable resources in the architectural design process.